Genetic association studies to detect adverse drug reactions: abacavir hypersensitivity as an example. (February 2009) - Hughes, Arlene R; Brothers, Cynthia H; Mosteller, Michael; Spreen, William R; Burns, Daniel K
Abacavir hypersensitivity (ABC HSR) is a treatment-limiting adverse event associated with the use of the antiretroviral medicine, abacavir. The objective of the ABC HSR pharmacogenetics program was to identify clinically useful genetic risk factors to predict an individual patient''s risk for ABC HSR. The major histocompatibility complex allele, HLA-B*5701, was identified retrospectively and confirmed with independent sample sets. The clinical utility of prospective HLA-B*5701 screening was demonstrated in a blinded randomized clinical trial and in open-label cohorts. Screening has been incorporated into clinical practice and the ABC HSR pharmacogenetics program has been highlighted as a success by pharmacogenetics researchers. Important lessons from this pharmacogenetics program will be discussed in this paper.